Marka iletişim bağlamında marka kimliği ve marka kimliğinin reklam dilinde kullanımının değerlendirilmesi - Karanfil, Özgür (My University, 2008)
Our country, striving for a place in the globalizing world, is a country at the crossroads of East-West, Asia-Europe, with much geopolitical and strategic importance, and open to all kind of cultural influences. “Language” as a means of communication is the most important factor in cultural exchange. At this point, advertisements appear to play an important role in this cultural exchange. Countries have different cultures, whereas some have similar ones. Some countries with their superiorities in culture, economy and other social dimensions have their effects on weaker ones. In the use of this power, we also witness the power of “language” in advertisements. Terms like “Five o'clock tea culture” or “the Mac Donald's culture” have found their places in our language and culture. In this paper, we try to stress, that the correct use of Turkish advertisement language is also important. The misuse of language without conscious, correct, proper and culturally relevant terms will cause failure of an advertisement. Companies with a worldwide success, always localize their advertisements, following the motto “think globally, act locally” by accessing different target communities. In this paper, we start with the hypothesis, that the proper use of advertisement language in producing a trademark identity will help lead that trademark to success, whereas the misuse of it will make a trademark identity unsuccessful and vanish in a short time. The language of trademark identity is established on a firm base by using the audio-visual, smell, taste and touch icons adequately and properly. The term of trademark language contains a wide area and many details of phenomena. The proper use of it secures the permanence of a trademark in the market, like the proper use of a national language secures the permanence of the national culture. x Leech classified ads as direkt address and indirect address, in terms of language use. Alexander classified them as hard method and moderate method ads. The names of the classifications may be different, but the content is the same. Exaggerated language modification is the most used form of language modification in turkish ads, whereas language structure is simple mainly. Another attractive feature is playing around in writing words, writing them wrong deliberately. In the research, direct address was seen in most cases. In this research, the 12 issues from year 2006 of the Elele journal are considered weak in terms of written ad language. This paper is limited to examples on printed matter (journals – esp. all issues of the Elele journal of year 2006 -, newspapers, books) and internet, published within the time period of its working out. KEY WORDS Trademark communication and its features trademark identity, trademark icons the use of the advertisement language the “Elele” Journal
Keywords: İletişim; Marka; Marka Kimliği; Reklam ve Tanıtım; Reklamcılık